COMMUNITY AND PUBLIC SPORTS AND LEISURE FACILITIES: POSSIBILITIES/DIFFICULTIES (Fiep Bulletin - online, 2025)
Introduction: The search for the use of public sports and leisure spaces enables individual, social and mental well-being in different social arrangements. However, factors such as work obligations and lack of access to places and equipment end up leaving time for leisure in second or third place. Objective: Analyze how the IFPI school community of Jose de Freitas-PI makes use of public sports/physical-sports spaces/equipment. Methods: Quantitative study of a descriptive, interpretative and bibliographical nature with approximately 45 students from the 1st and 2nd years of high school at the IFPI campus Jose de Freitas-PI. A Google Forms questionnaire was used with 11 closed questions. Data analysis was statistical, followed by organization and interpretation of graphs. Results: It is clear that the majority of schoolchildren are aware of the city's public sports and leisure spaces; Playfulness is an important point in relation to the attractive power of these spaces; Places that enable playfulness and sporting/physical leisure contribute to the development of the body culture of movement; Regarding the barriers arising from access to these sports and leisure equipment, we can identify structural conditions as the main one, followed by issues of self-interest and safety. Conclusion: The IFPI school community of Jose de Freitas-PI has a direct relationship with public sports and leisure spaces, however there are still problems to be resolved, mainly regarding the physical structures of such spaces and security, which probably constitutes the main barrier to access and use of these places.
Keywords: community; leisure activities; playfulness; vulnerability